Network lifetime analytical model for node-disjoint multipath routing in wireless sensor networks. (1st January 2013) - Murthy, Shiva G.; Souza, R.J.D.; Varaprasad, G.
The objective of every sensor node in a sensor network is to send the sensed data in the phenomena to a sink node. The network lifetime is maximal, when the energy consumption of each node is uniform. Many routing protocols select an optimal path to increase the network lifetime in sensor networks. The energy of the nodes along this optimal path is consumed more, causing their early death. In the multipath routing, data traffic is distributed among the multiple paths, instead of a single optimal path. This work proposes a theoretical frame work to study the node-disjoint multipath wireless sensor network reliability. With higher reliability, higher network lifetime can be achieved. Simulation results show that when the data is transmitted through multiple paths with different data rates, the network lifetime increases. The node criticality factor enhances the network lifetime analysis effectively.